Slovakia’s departure from strong labor protection of employees as a consequence of the pandemic and the transposition of european directives - Švec, Marek; Mészáros, Peter (Technium Social Sciences Journal, 2024)
This scientific paper delves into the notable shift in Slovak labor law, which has departed from its historically strong emphasis on safeguarding the rights of employees, traditionally seen as the weaker party in labor relations. Until recently, this emphasis served as a substantial barrier against the globalizing and standardizing influences of employers. The paper identifies two key factors driving recent legislative "reforms" in Slovakia’s labor regulation. These changes are rooted in the transposition of European labor law directives while also embracing a more liberal political perspective regarding the nature of labor relations. This shift involves moving away from rigid employee protection and adopting the concept of "increased flexibility" in employee work as a remedy for addressing the post-Covid-19 economic challenges. The previous emphasis on employee or employee representative involvement in defining working conditions, wages, and important employer decisions regarding work organization has shifted. This shift allows employers to act unilaterally, contingent on fulfilling new information obligations towards employees. However, the recent labor law reforms run counter to this historical legal tradition. Taking into account the wage levels in the Slovak Republic compared to the majority of other European Union member states, these reforms establish an unsettling level of labor law protection pro futuro of Slovak employees.